Answer:
1. x=6
2. x=9
Step-by-step explanation:
1.
[tex]-2(3x+9)=-54\\-6x-18=-54\\+18 +18\\-6x=-36\\\frac{-6x}{-6} = \frac{-36}{-6}\\x=6[/tex]
2.
[tex]2(3x+4)-3x=35\\6x+8-3x=35\\3x+8=35\\-8 -8\\3x=27\\\frac{3x}{3} =\frac{27}{3} \\x=9[/tex]
Written Explanation:
1.
-2x(3x+9)=-54
-6x-`8=54 (Distributive property)
Add 18 to both sides
-6x=-36
Divide both sides by -6 (negative divided by a negative equals a positive)
x=6
2.
2(3x+4)-3x=35
6x+8-3x=35 (distributive property)
3x+8=35 (combine Iike terms and then subtract them 6x-3x=3x)
Subtract 8 from both sides
3x=27
Divide both sides by 3
x=9